The use of formulaic language to enhance the speaking ability of limited English proficient (LEP) learners in a secondary school (IR) - Rathai A/P Muniandy@Perumal (2017)
This study is aimed to analyse on how formulaic language can be used to enhance the speaking ability of limited English proficient (LEP) learners in a secondary school. Five, Form 4 LEP learners were involved in this study, which used a mixed method with an embedded design methodology. Their speech production (monologue and dialogue) were analysed in terms of accuracy by looking into the sentence selection to convey their intended ideas and the level of correctness in employing the learnt formulaic language in terms of lexis choices, word order and grammar, before and after a series of direct instruction sessions, which involved noticing? and awarenessraising? activities. The study also analysed how the use of formulaic language affects the context of repair fluency of the LEP learners in terms of repetition, reformulation and false starts. It can be concluded that the use of formulaic sequences had improved the quality and length of speech production for all the five LEP learners of this study, and to a certain extent had also served as a time-gaining strategy in their repair fluency. Due to learner differences, they improved at different levels, and the use of formulaic sequences was more extensive in the monologue speech production after the direct instruction sessions. However, their dialogic speech did not show encouraging improvement as their monologue speech production. This study provided some insights on how teachers may explore the use of formulaic language in teaching speaking skills especially to learners with limited English proficiency.